2016
DOI: 10.1536/ihj.15-433
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intravascular Hemolysis With Erythrocyte Creatine in Patients With Aortic Stenosis

Abstract: SummaryChronic intravascular hemolysis has been identified in patients with cardiac valve prostheses, but only a few case reports have evaluated intravascular hemolysis in patients with native valvular heart disease. To detect intravascular hemolysis in patients with aortic stenosis, erythrocyte creatine was evaluated with hemodynamic indices obtained by echocardiography.Erythrocyte creatine, a marker of erythrocyte age, was assayed in 30 patients with aortic stenosis and 10 aged matched healthy volunteers. Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Several markers including fragmented red cell, reticulocyte, lactate dehydrogenase, indirect bilirubin, haptoglobin, and erythrocyte creatinine have been applied to estimate the severity of intravascular hemolysis [1][2][3][4][5][6][7][8][9][25][26][27]. Among these markers, lactate dehydrogenase has been widely used to estimate the severity of intravascular hemolysis, because close relation between lactate dehydrogenase and 51 Cr-labeling method has been demonstrated [2,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several markers including fragmented red cell, reticulocyte, lactate dehydrogenase, indirect bilirubin, haptoglobin, and erythrocyte creatinine have been applied to estimate the severity of intravascular hemolysis [1][2][3][4][5][6][7][8][9][25][26][27]. Among these markers, lactate dehydrogenase has been widely used to estimate the severity of intravascular hemolysis, because close relation between lactate dehydrogenase and 51 Cr-labeling method has been demonstrated [2,25].…”
Section: Discussionmentioning
confidence: 99%
“…
Intravascular hemolysis has been reported in heart valve replacement with mechanical prostheses, stenotic valve diseases, hypertrophic cardiomyopathy, and pulmonary hypertension [1][2][3][4][5][6][7][8][9]. Even in cases of subclinical anemia, intravascular hemolysis due to destruction of erythrocytes remains to be evaluated.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An excellent correlation between erythrocyte creatine and direct measurement of red blood cell survival time by 51 Cr method has been reported [12,13]. In patients with normal erythropoietic capacity such as intravascular haemolysis and haemolytic anaemia, red cell production is accelerated in proportion to the amount of erythrocyte destruction, which lead to an increase in the young erythrocytes containing higher erythrocyte creatine levels [26][27][28][29]. In contrast, renal anaemia is mainly caused by decreased erythoropoietic capacity due to inadequate erythropoietin production and/or hypoesponsiveness to rHuEpo treatment [6,30].…”
Section: Discussionmentioning
confidence: 99%
“…11) Similar phenomena have been detected in patients with severe aortic stenosis. 12) Previous studies have demonstrated that fHb scavenges nitric oxide (NO) and reduces the bioavailability of NO during hemolysis, thus leading to endothelial dysfunction and platelet activation. 13,14) At the same time, elevated fHb interacts with the A1 and 2 domains of von Willebrand factor (vWF), which increases platelet adhesion to vWF.…”
mentioning
confidence: 99%